2016
DOI: 10.1097/ccm.0000000000001616
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Corticosteroid Treatment in Adults With Influenza A (H7N9) Viral Pneumonia*

Abstract: High-dose corticosteroids were associated with increased mortality and longer viral shedding in patients with influenza A (H7N9) viral pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 33 publications
7
132
0
3
Order By: Relevance
“…Specific antiviral treatment was initiated early in this H7N4 case (5 days after onset of disease), compared with the median time of H7N9 patients (7 days) [22]. High-dose corticosteroid therapy (>150 mg/d methylprednisolone or equivalent) was reported to significantly increase mortality and viral shedding time of H7N9 patients [26]. In this case, the dose implemented was low to moderate (20-80 mg/d).…”
Section: Discussionmentioning
confidence: 84%
“…Specific antiviral treatment was initiated early in this H7N4 case (5 days after onset of disease), compared with the median time of H7N9 patients (7 days) [22]. High-dose corticosteroid therapy (>150 mg/d methylprednisolone or equivalent) was reported to significantly increase mortality and viral shedding time of H7N9 patients [26]. In this case, the dose implemented was low to moderate (20-80 mg/d).…”
Section: Discussionmentioning
confidence: 84%
“…Various studies reported that GCs administration in patients with severe influenza pneumonia was associated with a higher rate of mortality [40][41][42][43][44]. A meta-analysis conducted with a total of 6548 patients with influenza pneumonia (H7N9 or H1N1), found the use of systemic GCs (methylprednisolone with different dose ranges, when reported) associated with higher mortality rate (risk ratio [RR] 1.75, 95% confidence interval [CI] 1.30-2.36, Z = 3.71, P = 0.0002), longer intensive care unit permanence and higher rate of secondary infection [44][45][46]. Only trials in recruiting status were included about the use of Hydroxychloroquine.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…In comparison to controls who did not receive systemic corticosteroids, high‐dose systemic corticosteroids (defined as >150 mg/day methylprednisolone equivalent) was associated with increased risks of 30‐day mortality (38.5% vs 7.7%, P = 0.021) and 60‐day mortality (50% vs 15.4%, P = 0.022) and longer viral shedding (15 vs 13 days, P = 0.039) among patients with influenza A(H7N9) viral pneumonia. There was no difference between low dose (25–150 mg/day methylprednisolone) and controls …”
Section: Disclosure Statementmentioning
confidence: 85%